Monster hunt 2 [videorecording (DVD)] - Leung, Tony Chiu Wai, 1962-; Bai, Baihe, 1984-; Jing, Boran, 1989- (The Myth Entertainment, 2018)
The story continues with Wuba after he parts way with his human parents Tian and Lan for his own journey. Peace has not been restored in the monster world after the death of the evil monster king.